CHEMISTRY 1 : for PRE-UNIVERSITY - Chieng, Tiong Chin; Mohd Alhafiizh, Bin Zailani; Wan Roslina, Wan Yusof; Sharifah Mona, Binti Abd Aziz Abdullah (UNIMAS Publisher, 2018)
This book, Chemistry I, is specially tailored for Pre-University students in Universiti 7 Malaysia Sarawak who intend to pursue their studies in either biological or physical ) science courses. It covers all the topics of t h e course PR.KI 01 6, Chemistry I which is offered in Semester 1. This book provides a useful transition from sch ool to university level as well a s a suitable refer ence for STPM, A-level or a ny other pre-university and first year u niversity ch emistry courses.